Translational stroke research : from target selection to clinical trials - Zhang, John H.; Lapchak, Paul A. (Springer Series in Translational Stroke Research, 2012)
Translational Stroke Research: From Target Selection to Clinical Trials is part of "Springer Series in Translational Stroke Research." Forty-three chapters from leading stroke research groups around the world select future targets and methods for stroke management such as the vasculature and white matter, protein aggregation, neuroglobin, microRNAs, oxidation, soluble epoxide hydrolase, apoptosis, hypoxia-inducible factors, thrombin, toll-like receptor, angiogenesis, membrane potentials and pumps. The book discusses methods to regulate brain temperature and the use of preconditioning in stroke. It also presents new areas of research emphasizing restoration of function with growth factors and stem cells.  It provides multiple animal models of both ischemic and hemorrhagic stroke in order to translate basic preclinical findings to clinical trials with de-risking issues,  therapy delivery methods such as sustained-release and intranasal delivery, and potential therapies including cell therapies, albumin, transcranial laser, microbubbles, and ultrasound. Finally, it debates clinical trial design for analytical methodology, imaging, computation, and innovations.